The Effect of Manure Dosage on the Growth and Yield of Shallot Plants (Allium ascalonicum L.) in Subak Dangin Umah, Batubulan Kangin Village - Dewa Ayu Ari Febriyanti; Ni Ketut Karina Sari (International Conference on Multidisciplinary Research Perspective, 2025)
Shallots (Allium ascalonicum L.) are a strategic commodity whose productivity in Indonesia is often constrained by declining soil fertility due to the intensive use of inorganic fertilizers. As a sustainable solution, this study evaluated the effect of manure application on the growth and yield of shallots. The research utilized a Randomized Block Design (RBD) with four dosage treatments: D0 (0 tons/ha), D1 (10 tons/ha), D2 (20 tons/ha), and D3 (30 tons/ha). It was conducted in Subak Dangin Umah, Batubulan Kangin Village, Gianyar, Bali, from April to July 2025. Key variables measured included vegetative growth and yield per hectare. The analysis results showed that manure application had a significant effect on both growth and yield. Treatments D2 (20 tons/ha) and D3 (30 tons/ha) resulted in significantly higher vegetative growth and bulb yield compared to the control (D0). Fresh bulb weight increased significantly from 2.9 kg/plot (control) to 4.7 kg/plot (D2) and 5.0 kg/plot (D3). Although the 30 tons/ha dose produced the highest bulb weight, the yield increase was relatively small compared to the 20 tons/ha dose. Therefore, 20 tons/ha is recommended as the economically more efficient optimum dose. In conclusion, the use of manure not only boosts shallot yield but also supports soil quality improvement and the sustainability of the subak farming system in Bali.